Raman signal enhancement tunable by gold-covered porous silicon films with different morphology - Agafilushkina, Svetlana N.; Zukovskaja, Olga; Dyakov, Sergey A.; Weber, Karina; Sivakov, Vladimir; Popp, Jürgen; Cialla-May, Dana; Osminkina, Liubov A. (Sensors, 2020)
The ease of fabrication, large surface area, tunable pore size and morphology as well surface modification capabilities of a porous silicon (PSi) layer make it widely used for sensoric applications. The pore size of a PSi layer can be an important parameter when used as a matrix for creating surface-enhanced Raman scattering (SERS) surfaces. Here, we evaluated the SERS activity of PSi with pores ranging in size from meso to macro, the surface of which was coated with gold nanoparticles (Au NPs). We found that different pore diameters in the PSi layers provide different morphology of the gold coating, from an almost monolayer to 50 nm distance between nanoparticles. Methylene blue (MB) and 4-mercaptopyridine (4-MPy) were used to describe the SERS activity of obtained Au/PSi surfaces. The best Raman signal enhancement was shown when the internal diameter of torus-shaped Au NPs is around 35 nm. To understand the role of plasmonic resonances in the observed SERS spectrum, we performed electromagnetic simulations of Raman scattering intensity as a function of the internal diameter. The results of these simulations are consistent with the obtained experimental data.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Gold; Plasmonics; Porous silicon; Sensorics; Surface-enhanced Raman scattering